Buprenorphine medication-assisted treatment during pregnancy: An exploratory factor analysis associated with adherence. (1st November 2018) - Coker, Jessica L.; Catlin, David; Ray-Griffith, Shona; Knight, Bettina; Stowe, Zachary N.
Highlights: Majority of pregnant women adhered to buprenorphine treatment until delivery. Higher clinically rated withdrawal symptoms are associated with non-adherence. Co-morbid psychiatric illness and childhood trauma did not impact adherence. Inpatient induction of buprenorphine during pregnancy did not improve adherence. Abstract: Background: : The treatment of pregnant women with opioid use disorder is challenging due to the myriad of physical, mental, and social complications. Factors influencing adherence to buprenorphine during pregnancy have not been identified. Materials and methods: : Pregnant women with opioid use disorder followed in a tertiary clinic were included in a retrospective chart review from buprenorphine induction through delivery. All women who had been evaluated and treated with buprenorphine from January 1, 2014, to September 31, 2016, were included. Adherence was defined as follows: 1) adherent: attended follow up visits, negative urine toxicology screens, and phase advancement; 2) moderately adherent: attended follow up visits until delivery, had not completed six negative urine toxicology screens, or had positive urine toxicology screens (i.e., no phase advancement); 3) non-adherent: missed follow up visits and did not stay in treatment until delivery. Sociodemographic characteristics, family psychiatric history, current and lifetime psychiatric and childhood trauma along with treatment factors were compared by category of adherence. Results: : 64 women met criteria for inclusion in this study with 41 (64%) adherent; eight (13%) moderately adherent; and 15 (23%) non-adherent. In the non-adherent group compared to the adherent group, the clinician-rated opioid withdrawal scale score was significantly higher, and the daily buprenorphine dose at last visit was significantly lower. Conclusions: : Women who were non-adherent to buprenorphine during pregnancy had higher severity of opioid withdrawal symptoms and lower doses of buprenorphine. These findings should be further explored with the goal of optimizing care without increasing risk for neonates.